Chemically induced hypoxia promotes differential outcomes over preadipocyte– or adipocyte–macrophage communication. (27th May 2017) - Avila-George, K.; Ramos-Olivares, K.; Vasquez-Munoz, K.; Villanueva-Morales, V.; Reyes-Farias, M.; Quintero, P.; Garcia, L.; Garcia-Diaz, D. F.
Abstract: Expansion of white adipose tissue induce insufficient vascularization, driving hypoxia and low-grade inflammation. Resident preadipocytes are thought to be involved. We evaluated the effects of hypoxia over preadipocytes and adipocytes, to determine which cellular type impacts the most over macrophages activation. 3T3-L1 cells were either differentiated, or maintained undifferentiated. Each group was subjected to the presence or absence of chemical hypoxia (200 μM CoCl2 ) for 24 h. Conditioned media were used as treatment for murine RAW264.7 macrophages for 24 h. Gene expression of HIF-1α and TNF-α, and the release of several markers were assessed. It was observed that culture media from hypoxic preadipocytes induced greater expression of inflammatory markers and NO release than culture media from hypoxic adipocytes, by macrophages. Gene expression correlated closer with inflammatory markers release specially on macrophages treated with conditioned media from preadipocytes. Hence, the present work highlights the importance of preadipocytes on inflammatory conditions in vitro .